Analisis Profesionalisme Guru dalam Menggunakan Metode Pembelajaran di SDN 060909 Medan Denai - Suciari, Adinda Dwi; Anjani, Alifa Dwi; Sabila, Aufa; Khairi JS, Kinasih; Elovany Sipayung, Geby Thasya (UNIVERSITAS SERAMBI MEKKAH, 2025)
As a teaching staff, a teacher must have professional abilities in the field of learning to create an effective and meaningful learning process for students. This writing aims to find out the level of professionalism of teachers at SD 060909 Medan Denai, the motivation and goals of a person to become a teacher, the learning methods used, and the difficulties faced in applying these methods. This research was conducted at SDN 060909 Medan Denai with the research subject of Class 4 Teacher. The data collection techniques used include interviews, observation, and documentation. The data obtained were analyzed using the stages of data reduction, data presentation (data display), and conclusion drawing or verification. Based on the research, the Grade 4 Teacher is not a graduate of Elementary School Teacher Education (PGSD) but Physics Education, and has not participated in the Teacher Professional Education (PPG) program because the working period is less than five years. However, being an elementary school teacher has been her goal since high school, so she is dedicated to this profession. The learning methods used are lecture and question and answer, but they are considered ineffective because they make students bored. Teachers feel the need for a variety of methods to increase students' interest in learning. Another difficulty is directing students to stay focused, which is influenced by their dependence on social media. This reduces students' attention while learning and time for schoolwork. The research emphasizes the need for teacher training and innovation in learning methods to overcome these barriers